Tarihimiz ve biz - Ortaylı, İlber, 1947-; Koçal, Adem; Akbıyık, Neval (İstanbul : Timaş Yayınları, 2014)
İÇİNDEKİLER
Keywords: Osmanlı İmparatorluğu -- Tarih -- 1288-1918.; Ottoman Empire -- History -- 1288-1918.; Türkiye -- Tarih -- Osmanlı İmparatorluğu, 1218-1918.